2015
DOI: 10.1016/j.nbd.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of adolescent alcohol exposure-induced amygdaloid histone modifications in anxiety and alcohol intake during adulthood

Abstract: Binge drinking is common during adolescence and can lead to the development of psychiatric disorders, including alcoholism in adulthood. Here, the role and persistent effects of histone modifications during adolescent intermittent ethanol (AIE) exposure in the development of anxiety and alcoholism in adulthood were investigated. Rats received intermittent ethanol exposure during post-natal days 28-41, and anxiety-like behaviors were measured after 1 and 24 hrs of the last AIE. The effects of AIE on anxiety-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
265
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(292 citation statements)
references
References 68 publications
24
265
3
Order By: Relevance
“…Interestingly, infusion of HDAC2 siRNA in the CeA of alcohol-preferring rats was able to correct the deficits in BDNF levels and attenuated excessive alcohol drinking behaviors. Together, these studies support the notion that BDNF gates alcohol drinking behaviors (1, 36, 9, 10). …”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, infusion of HDAC2 siRNA in the CeA of alcohol-preferring rats was able to correct the deficits in BDNF levels and attenuated excessive alcohol drinking behaviors. Together, these studies support the notion that BDNF gates alcohol drinking behaviors (1, 36, 9, 10). …”
Section: Figuresupporting
confidence: 77%
“…The epigenetic regulation of BDNF also plays a crucial role in early life adversity, such as adolescent alcohol exposure, which produces a persistent decrease in the expression of BDNF and Arc and dendritic spines in the CeA and MeA due to HDAC2-mediated deficits in histone acetylation in adulthood. These changes are associated with adolescent alcohol exposure-induced anxiety and alcohol drinking behaviors in adulthood that are attenuated by HDAC inhibitor treatment (10). As discussed by Warnault et al (1), low blood levels of BDNF have been associated with the severity of alcoholism in clinical populations.…”
mentioning
confidence: 99%
“…The open field activity scores for most of the tests were significantly altered with early binge drinking in the Intact rats,GX-TP and GX rats, and our results supported studies showing an alcohol-induced increase in anxiety-like behaviours in male rats. Similar results have also shown,in the LDB and EPM behavioural tests, that adolescent intermittent ethanol induced anxiety-like behaviours in adulthood [29]. These results indicated that binge drinking produced anxiety-like behaviours during adolescence that persisted into adulthood.…”
Section: Discussionsupporting
confidence: 85%
“…Intermittent access to drugs of abuse results in altered behavioral responses in comparison to continued administration (Marec et al, 2011), and intermittent exposure administration procedures are commonly used to study alcohol effects (Pandey et al, 2015; Risher et al, 2015). Having assessed adaptations in cytokine responses that occur with repeated once-daily exposure to ethanol, we next examined whether the schedule of ethanol exposure would impact cytokine expression patterns in the CNS.…”
Section: Methodsmentioning
confidence: 99%